Agelasines B, D and antimicrobial extract of a marine sponge Agelas sp. from Tahuna Bay, Sangihe Islands, Indonesia - Walter Balansa; Stevy Imelda Murniati Wodi; Frets Jonas Rieuwpassa; Frans Gruber Ijong (Society for Indonesian Biodiversity, 2020)
Abstract. Balansa W, Wodi SIM, Rieuwpassa FJ, Ijong FG. 2020. Agelasines B, D and antimicrobial extract of Agelas sp. from Tahuna Bay, Sangihe Islands, Indonesia. Biodiversitas 21: 699-706. The alarming growth of antibiotic-resistant bacteria necessitates the discovery of new antibiotics including those for combating life-threatening ESKAPE (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacter sp) and fish pathogenic bacteria. This study aimed to identify antimicrobial compounds from an extract of a marine sponge collected from Enepahembang coral reef, Sangihe Islands, North Sulawesi, Indonesia. The sponge was identified by DNA barcoding as Agelas sp. and its extract was evaluated against three ESKAPE bacteria (S. aureus, K. pneumoniae, and A. baumannii) and three fish pathogenic bacteria (A. hydrophila, Edwardsiella tarda and Vibrio parahaemolyticus), using the standard disk diffusion method. It showed moderate to strong antimicrobial activity against S. aureus (25.3 mm), K. pneumoniae (15.5 mm), A. baumannii (20.2 mm), A. hydrophila (20.5 mm), E. tarda (22.4 mm) and A. salmonicida (21.2 mm). The extract was isolated by chromatographic techniques (column chromatography, flash chromatography, and high-performance liquid chromatography). The structures and relative stereochemistry of the two compounds were elucidated by HRESIMS, 1D and 2D NMR data analysis as well as by comparison with reported values. Unfortunately, limited amount of the pure compounds prevented us from further evaluating their antimicrobial activity against the test bacteria. Nevertheless, the crude extract's strong antimicrobial activity, especially against the test Gram-negative bacteria, suggests the importance of this finding in light of the recent antimicrobial drug scarcity but rapid antimicrobial resistance and the emerging paradigm of antimicrobial drug modification, redirection and/or repurposing for discovering new antibiotics particularly against the life-threatening Gram-negative bacteria.